Dynamic poverty decomposition analysis: An application to the Philippines - Tomoki Fujii (Asian Development Bank Institute (ADBI), 2014)
In this paper, we propose a new method of poverty decomposition. Our method remedies the shortcomings of existing methods and has some desirable properties such as timereversion consistency and subperiod additivity. It integrates the existing methods of growthredistribution decomposition and sector-based decomposition, because it allows us to decompose the change in poverty into growth and redistribution components for each group (e.g., regions or sectors) in the economy. We extend our method to include six components and provide an empirical application to the Philippines for the period 1985 - 2009.
Keywords: I32; O10; 330; economic growth; foster-greer-thorbecke (fgt) measure; inequality; inflation; poverty profile; watts measure